105 ALTERATIONS IN REGIONAL WALL STRAIN, ENOS AND MICROTUBULIN CONCENTRATIONS SIGNALING LEFT VENTRICULAR REMODELING OCCUR IMMEDIATELY AFTER ACUTE MYOCARDIAL INFARCTION. (1st January 2005) - Phan, H.; Juneman, E.; Castellano, L.; Johnson, N.; Goldman, S.; Gaballa, M.; Thai, H.
Abstract : Background: Left ventricular (LV) remodeling after myocardial infarction (MI) leads to heart failure (HF). While alterations in LV wall strain are seen in the infarcted regions (IR), it is unclear if this also affects the non-infarcted regions (NIR) of the LV. Additionally, while LV tissue eNOS and constituitive microtubulin (CM) are altered in chronic HF, it is unknown what happens to these biomarkers acutely. We evaluated changes in LV wall strain; myocardial eNOS and CM acutely post MI. Methods: LV wall motion of Sprague Dawley rats (N = 10) was analyzed by echocardiography at several time points after MI. Hemodynamic measurements were obtained via a Millar catheter. Alterations in myocardial contraction (δ strain) are measured via M-mode echocardiography. CM and eNOS were determined via immunoblot techniques. Results: Systolic blood pressure decreased (P ≤ 0.05) acutely post MI (127.1 ± 6.1 vs 101.7± 10.1 mmHg). LV end diastolic pressure increased (P≤0.05) acutely after MI (5.8 ± 0.5 vs. 19.9 ± 2.0 mmHg). These changes were accompanied by a decrease (P≤ 0.05) in LV dP/dt after MI (7106 ± 520 vs. 4671± 350, mmHg/sec). δ strain was decreased in the anterior IR immediately (0.15 ± 0.04 vs 0.1 ± 0.02 mm, P ≤ 0.01); similarly δ strain was also decreased in the posterior NIR starting at 1 minute (0.17 ± 0.02 vs 0.1 ± 0.02 mm, P ≤ 0.01). A decrease in eNOS was seen with both the IR and NIR of the LV (20.8± 3.8 intensity unit (IU)/50 μg of tissue vs 11.1 ± 3.3 IU/50 μg, P = 0.04) and (26.7 ± 4.8 vs 8.14 ± 1.6 IU/50 μg, P = 0.002), respectively after MI. Conversely, CM was increased in both IR and NIR of the LV (10.3 ± 2.4 IU/25 μg vs 26.2 ± 4.6 IU/25 μg, P = 0.0005) and (9.3 ± 1.8 vs 18.5 ± 3.7 IU/25 μg, P = 0.003), respectively. Conclusion: Decreases in δ strain occurred in both IR and NIR of the LV acutely after MI. This is accompanied by alterations in eNOS and CM levels throughout the LV immediately after MI. Our data demonstrate that physical and biomarkers signaling LV remodeling occur immediately after MI, rather than over time.